2014
DOI: 10.1007/s11483-014-9350-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH and NaCl on the Emulsifying Properties of a Napin Protein Isolate

Abstract: The physicochemical and emulsifying properties of a napin protein isolate (NPI) were examined as a function of pH (3.0, 5.0 and 7.0) and NaCl content (0, 50 and 100 mM). Specifically, surface charge and hydrophobicity, interfacial tension (IT), solubility, and the emulsifying activity (EAI) and stability (ESI) indices were studied. Surface charge in the absence of NaCl ranged between~+10 mV to~−5 mV depending on the pH, becoming electrically neutral at pH 6.6. Overall, surface hydrophobicity decreased as the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…Presence of phytates in canola protein isolate composed of cruciferin and napin (70% globulin, 30% albumin and ∼1% phytic acid) may cause stable electrostatic protein-phytate complexes thus reduces surface activity of protein molecules (Krause and Schwenke, 2001) and enhance interface stabilization. Working with somewhat pure protein, Wu and Muir (2008) and Cheung et al (2014) showed cruciferin (>80% purity) possesses better emulsifying ability than napin (Cheung et al, 2015). Wijesundera et al (2013) demonstrated that canola protein extracted at alkaline pH (12) and recovered by precipitating at pH 6.5 can stabilize O/W emulsions.…”
Section: Oil/water (O/w) Emulsionsmentioning
confidence: 99%
“…Presence of phytates in canola protein isolate composed of cruciferin and napin (70% globulin, 30% albumin and ∼1% phytic acid) may cause stable electrostatic protein-phytate complexes thus reduces surface activity of protein molecules (Krause and Schwenke, 2001) and enhance interface stabilization. Working with somewhat pure protein, Wu and Muir (2008) and Cheung et al (2014) showed cruciferin (>80% purity) possesses better emulsifying ability than napin (Cheung et al, 2015). Wijesundera et al (2013) demonstrated that canola protein extracted at alkaline pH (12) and recovered by precipitating at pH 6.5 can stabilize O/W emulsions.…”
Section: Oil/water (O/w) Emulsionsmentioning
confidence: 99%
“…However, there is an increasing consumer demand for more natural, environmentally friendly, and sustainable commercial products [7]. Many manufacturers are reformulating their products to replace the synthetic surfactants with more label-friendly natural alternatives [8] or to replace animal proteins from with plant proteins [9,10]. Generally, manufacturers would often like to create new products entirely from natural ingredients so that they can make "all-natural" claims on their labels.…”
Section: Introductionmentioning
confidence: 99%
“…) and due to the innate behaviour related to the process set‐up. Enhanced solubility of NRP by the addition of NaCl is not expected, as also previously described in literature (Cheung et al ., ). NRP has therefore not been further examined in this study.…”
Section: Resultsmentioning
confidence: 97%
“…(), reporting that varying solubility at similar pH values is found. Different laboratory‐scale studies have analysed the possibility to enhance the solubility of rapeseed protein by, for example, partial hydrolysis (Vioque et al ., , ) and the addition of NaCl (Cheung et al ., , ).…”
Section: Introductionmentioning
confidence: 99%